The Effect of Position Promotion on Employee Spirit at PT Bank Negara Indonesia tbk : Study Case of Tebing Tinggi Branch Office - Cico Valangi Monthi (Institute of Computer Science (IOCS), 2022)
Nowadays, promotion is a very powerful motivator to increase employee morale at work. Promotion of a person's position must have competence in accordance with the results of his work, PT Bank Negara Indonesia, Tbk at the Tebing Tinggi Branch has carried out promotions to its employees. As a bank that prioritizes service, it has become something that is required so that employees can work as much as possible. The hypothesis of this study is that promotion has a positive and significant effect on employee morale at PT Bank Negara Indonesia, Tbk Tebing Tinggi Branch. This study uses the theory of human resource management related to job promotion and morale. The approach in this research is a survey. This type of research is descriptive quantitative. The nature of this research is explanatory, where the variables are measured by the lickert scale. Data collection techniques with a list of questions and interviews with 36 respondents. The results of the study indicate that promotion has a positive and significant effect on employee morale at PT Bank Negara Indonesia, Tbk Tebing Tinggi Branch